Modelling social system for school effectiveness - Dahiru, Abbas Sani; Basri, Ramli; Aji, Abubakar Abba; Asimiran, Soaib (Human Resource Management Academic Research Society, 2018)
School effectiveness is the level at which school is able to accomplish its pre-determined objectives with a view to solving the obstacles that might hinder the smooth running of schools. Although, substantial progress was theoretically achieved in defining effective schools, still there exists a dearth in models which researchers could rationalise and develop a theory that could best describe the phenomena. This paper explained the concepts of school effectiveness and social system as well as the role of social system theory in enhancing an effective school system. And finally the implications of the paper to the body of knowledge, policy makers and school principals were discussed in the paper.